Peran Religiusitas dalam Memoderasi Faktor-Faktor yang Mempengaruhi Akuntabilitas Pengelolaan Dana Desa - Rohmah, Awaliyah Mualisatur; Citradewi, Adelina (Universitas Palangka Raya, 2025)
This study aims to analyze and compare the influence of the government's internal control system, accounting information systems, and the use of information technology on the accountability of village fund management, with the religiosity of village officials as a moderating variable. The research applied a comparative quantitative approach using primary data collected through questionnaires distributed to 69 respondents, including village heads, village secretaries, and financial staff in the Tahunan and Mlonggo Districts of Jepara Regency. The sampling technique employed was saturation sampling based on specific criteria. The collected data were then processed and analyzed using Partial Least Square (PLS) with the SmartPLS software. The results revealed that the government's internal control system and accounting information systems have a positive and significant effect on the accountability of village fund management, while the use of information technology had no significant impact. Furthermore, religiosity was found to moderate the relationship between the internal control system and accountability, but failed to moderate the relationship between accounting information systems and the use of information technology on accountability. These findings emphasize the importance of integrating religious values with improved technical competencies of village officials to achieve transparent and accountable village financial management. Future research is suggested to broaden the research area, add new variables, and implement a mixed methods approach for more comprehensive results.